Designing an acoustic feedback system for on-water rowing training - Schaffert, N.; Mattes, K. (International Journal of Computer Science in Sport, 2011)
Analysis of measured kinematic parameters is commonly used in competitive sports to optimize athletes' performance. The progress in technology offers new ways for displaying feedback information to athletes. In rowing, synchronous visual feedback is regularly used, but the presentation of acoustic information is a new and promising application for technique training and monitoring. This paper describes the prototype Sofirow as an online acoustic feedback system for on-water rowing training, developed in cooperation between the University of Hamburg and BeSB GmbH Berlin. Sofirow measures propulsive boat acceleration (MEMS sensor, up to 125Hz) and velocity (4Hz-GPS). Technical requirements concerned with the acoustic transformation (sonification) and its presentation. The associated software Regatta provides an analysis of the measured data. An intra-cyclic analysis of the boat's acceleration-time-trace investigated potential benefits for the time structure of the acceleration trace. Effects on boat motion were explored in an empirical investigation with the German junior national rowing team in 2009. The first significant results were encouraging and support the implementation of acoustic information regularly into training processes for elite athletes. Sofirow represents the rhythmic acceleration trace distinctly and audibly and thus, offers systematic monitoring and control of the boat motion in on-water technique training.